Evaluation of stabilizing material and stabilization efficiency through comparative study of toxic heavy metal transfer between corn and peanut grown in stabilized field soil. (15th April 2021) - Lee, Yonghyeon; Cui, Mingcan; Son, Younggyu; Ma, Junjun; Han, Zhengchang; Khim, Jeehyeong
Abstract: Soil contaminated with toxic heavy metals (THMs) was stabilized by adding a combination of waste resources in 7.0 wt%, including coal-mine drainage sludge, waste cow bone, and steelmaking slag, in the ratio of 5:35:60. Subsequently, corn and peanut were cultivated in treated soil to investigate the effects of the waste resources on THM mobility in soil and translocation to plants. Sequential extraction procedures (SEP) was used to analyze mobile phase THMs which could be accumulated in the plants. SEP shows that mobile Pb, Cd, Cu, Zn, Ni, Cr, and As were reduced by 8.48%, 29.22%, 18.85%, 21.66%, 4.58%, 62.78%, and 20.01%, respectively. The bioaccumulation of THMs was clearly hindered by stabilization; however, the increment in the amount of immobile-phase THMs and change in the amount of translocated THMs was not proportional. The corn grains grown above the soil surface were compared with the peanut grains grown beneath the soil surface, and the results indicating that the efficiency of stabilization on THM translocation may not depend on the contact of grain to soil but the nature of plant. Interestingly, the results of bioaccumulation with and without stabilization showed that the movement of some THMs inside the plants was affected by stabilization. Graphical abstract: Image 1 Highlights: The waste resources effectively stabilize the mobile toxic heavy metals in the soil. Metal bioaccumulation was reduced when plants were cultivated in stabilized soil. Peanut and corn showed the different THM translocation behaviors. The movement of some THMs inside the plants was affected by stabilization.